Manajemen Risiko: Deteksi Dini Upaya Pencegahan Fraud - Sudarmanto, Eko (Jurnal Ilmu Manajemen, 2020)
The economic costs of fraud in financial statements continue to be a problem for organizations and the public. The problem discussed in this study is limited risk management strategies to detect early for the prevention of fraud made by company managers and auditors. This strategy is important for proactive fraud prevention and for the integrity of financial statements in the future. The aim of this multi-case qualitative study is to explore early detection and methods of preventing fraud on financial statements using a conceptual framework of risk management. As a conclusion, there is a gap in the concept of risk management in current practice to detect and prevent fraud, and how the auditor's perspective in creating a proactive anti-fraud model. In addition, with this finding practitioners can develop proactive antifraud risk management procedures, and for auditors can develop early detection guidelines in fraud prevention